When reduced input leads to delayed acquisition: a study on the acquisition of clitic placement by Portuguese heritage speakers - Flores, Cristina (2014)
This article examines the competence of heritage speakers of Portuguese living in Germany with respect to clitic placement in Portuguese by comparing their performance with that of monolingual speakers of the same age (7–15 years of age) in a test designed to elicit oral production data. The results of the study indicate that the heritage speakers go through stages in the acquisition of clitic placement that are similar to those of monolingual acquirers even though they take longer to attain the target grammar.